EFFECTS OF INTEGRATED USE OF VETIVER GRASS STRIPS AND MULCH ON SOIL EROSION AND MAIZE GRAIN YIELD IN IKENNE, NIGERIA (2016)
Soil erosion is a major threat to sustainable agriculture in the humid tropics. Management practices adopted to control soil erosion and improve soil quality include mulching and the use of Vetiver Grass Strips (VGS). Integrating VGS with mulch could be more effective in controlling soil erosion than VGS or mulching alone. However, information on the effectiveness of combined utilisation of VGS and Vetiver Mulch (VM) in controlling soil erosion and improving crop yield is scanty. Therefore, this study was carried out to quantify the effects of integrating VGS and VM on soil erosion, soil quality and maize Grain Yield (GY). Three soil erosion control experiments were conducted on a Rhodic Kandiudult soil with 7% slope, in Ikenne, using maize as test crop. Treatments in each experiment were laid out in a randomised complete block design with three replications. The potential of VGS spaced at 10 m intervals (10VGS) and 6 t/ha of VM (VM6) in reducing runoff, soil and nutrient losses was evaluated. Treatment with No Vetiver grass (NV) served as control. Runoff and soil loss were measured. Carbon, nitrogen and phosphorus contents of eroded sediment were determined using standard methods. In another experiment, 10VGS and VGS spaced at 20 m intervals (20VGS) were integrated with VM of 2 (VM2) and 4 (VM4) t/ha as: 10VGS+VM2, 10VGS+VM4, 20VGS+VM2 and 20VGS+VM4. The four integrated treatments and 10VGS, 20VGS, VM2, VM4, VM6 and NV were evaluated for their effectiveness in reducing erosion. Data were collected on soil loss and maize GY. Soil Physical Quality Index (SPQI) was estimated using the soil management assessment framework. Also, 10VGS+VM4, 10VGS, VM6 and NV were assessed for their effectiveness in reducing nitrate-N and phosphate-P in runoff. The nitrate-N and phosphate-P concentrations were determined using standard methods, and Eutrophic Quality Index (EQI) estimated. Data were analysed using descriptive statistics and ANOVA at α0.05. Runoff from 10VGS, VM6 and NV were 20.5±5.4, 16.9±6.7 and 30.9±2.3 mm while soil losses were 337.5±9.9, 402.5±40.0 and 1079.0±18.3 kg/ha, respectively. Carbon, nitrogen and phosphorus contents of eroded sediments for VM6 (12.65 g/kg, 1.25 g/kg and 7.60 mg/kg) and NV (16.90 g/kg, 1.70 g/kg and 8.30 mg/kg) were higher than for 10VGS (11.05 g/kg, 1.15 g/kg and 7.30 mg/kg). Soil loss was lowest under 10VGS+VM4 (1.48±0.06 t/ha/yr) and highest under NV (7.49±0.94 t/ha/yr). Soil loss increased in the order of 10VGS+VM4 <10VGS+VM2 <10VGS <VM6 <20VGS+VM4 <VM4 <20VGS+VM2 <20VGS <VM2 <NV. The SPQI was highest for 10VGS+VM4 (0.78±0.02) and lowest for NV (0.51±0.01). Maize GY on 10VGS+VM4 (1.73±0.35 t/ha) was significantly higher than other treatments with the lowest GY obtained on NV (0.91±0.04 t/ha). Nitrate-N and phosphate-P in runoff ranged from 2.11±0.07 (10VGS+VM4) to 2.97±0.23 mg/L (NV) and 0.014±0.001 (10VGS+VM4) to 0.026±0.002 mg/L (NV), respectively. The EQI ranged from 42.1 (10VGS+VM4) to 83.1% (NV). Integration of vetiver grass strips at 10 m intervals with vetiver mulch at 4 t/ha effectively controlled soil erosion, minimised water and nutrient losses, improved soil physical quality and maize grain yield in Ikenne. Keywords: Vetiver grass, Nitrate-nitrogen in runoff, Eutrophic quality index, Soil loss Word count: 494